A CRISPR/Cas12a-based DNAzyme visualization platform for rapid discrimination of Streptococcus suis serotype 2 versus 1/2 and serotype 1 versus 14 - Sun, Jing; Bai, Jieyu; Huang, Yuxuan; Langford, Paul R.; Zhang, Yueling; Li, Gang (Talanta (Oxford), 2025)
Streptococcus suis is a major swine pathogen with serotypes 2 and 14 posing zoonotic risks. However, distinguishing serotypes 1/2 from 2 or 1 from 14 remains challenging due to high similarity in their capsule polysaccharide (CPS) loci. Here, we developed a rapid, equipment-free discriminating platform targeting a single nucleotide polymorphism (SNP) at position 483 of the cpsK gene (G in serotypes 2/14 vs. T/C in 1/2/1). The method integrates recombinase polymerase amplification (RPA) with CRISPR/Cas12a and a G-quadruplex-hemin DNAzyme visualization system. RPA enables isothermal amplification, while CRISPR/Cas12a ensures single-nucleotide specificity by cleaving target DNA. Subsequent DNAzyme catalysis converts colorimetric substrates, enabling naked-eye differentiation via distinct color changes (blue for serotypes 1/2/1 vs. colorless for 2/14). This approach achieved a sensitivity of 101-102 copies per reaction and demonstrated 100 % specificity across 29 S. suis serotypes and related strains. Compared to PCR-based or sequencing methods, our platform eliminates reliance on thermocyclers or fluorescence detectors, reducing costs and operational complexity. The entire workflow, completed within 70 min, offers a practical solution for point-of-care testing in resource-limited settings. By enabling rapid, accurate discrimination, this tool will become a complementary tool for resolving ambiguous serotypes and enhances outbreak management in swine populations and mitigates zoonotic transmission. [Display omitted] •CRISPR/Cas12a system in conjunction with a G4 DNAzyme for rapid discrimination of S. suis serotype 2 and 1/2 or 1 and 14.•Employing a single nucleotide polymorphism (SNP) at position 483 of the cpsK gene.•Rapid identification within 70 min without the need for expensive instruments.•Versatile readout styles (naked eye, fluorescence) are available.•Excellent prospects for deployment in field-based point-of-care detection as well as in diagnostic laboratories.